Mangrove Restoration as an Implementation of Environmental Legal Responsibility: a Critical Analysis of Law No. 32 of 2009 on Environmental Protection and Management - Adillah Fajar Siddiq; Mhd Al-Israq Manik; Abdul Rahman M Siregar (SEAN Institute, 2025)
Mangrove ecosystems play a crucial role in maintaining coastal ecological balance, protecting biodiversity, and mitigating the impacts of climate change. However, increasing environmental degradation and land-use changes have led to severe mangrove deforestation in Indonesia. This paper critically analyzes the implementation of Law No. 32 of 2009 on Environmental Protection and Management in relation to mangrove restoration efforts. By adopting a juridical-normative approach combined with a socio-legal perspective, the study explores the extent to which legal frameworks have been effectively translated into actionable restoration programs. The analysis highlights both the strengths and gaps in the current regulatory system, including the lack of law enforcement, weak institutional coordination, and limited community participation. It is found that while the law provides a strong foundation for environmental responsibility, its practical implementation remains inconsistent and fragmented. Strengthening policy integration, enhancing local governance, and promoting collaborative restoration initiatives are key to ensuring that mangrove rehabilitation aligns with Indonesia’s legal obligations. This study contributes to the discourse on environmental governance by emphasizing the need for legal reforms and policy coherence in achieving sustainable coastal ecosystem restoration.